BIO-INFORMATIONAL ASPECTS IN ORGANIZATION OF FUNCTIONAL RESERVES OF ORGANISM FROM THE POINT OF THE THEORY OF FUNCTIONAL SYSTEMS - A. N. Kurzanov (Кубанский научный медицинский вестник, 2016)
The article analyses bio-informational aspects in organization of reserve abilities of organism. The author gives an overview of the existing ideas about the role of bio-information in supporting vital resources of the organism and providing its existence while interacting with the environment. The article discusses the role of signal communication of organismic level in organization of adaptive reactions aimed at satisfying the needs of organism, including the formation of its functional reserves. Form the point of the theory of functional systems, it is logically grounded that functional reserves of organism can be considered as a dynamically self-regulating complex of informative elyinterrelated functional systems, whose multifaceted interaction provides the mobilization and recovery of the reserve abilities, in accordance with the vital needs of organism.